Patients' experiences of an open access follow up arrangement in managing inflammatory bowel disease. Issue 5 (1st October 2004) - Rogers, A; Kennedy, A; Nelson, E; Robinson, A
Abstract : Background: Improving access is a key policy issue in improving quality of care and extending patient choice and participation. People's experience of changing from fixed outpatient appointments to more flexible direct access arrangements for chronic disease has been underexplored. Objectives: To examine patients' views on using an open system of access compared with fixed outpatient appointments as part of a guided self-management intervention for inflammatory bowel disease (IBD). Design: Embedded qualitative study undertaken alongside a randomised controlled trial. Semi-structured interviews were undertaken to obtain an in depth understanding of patients' experience of the change in access arrangements. Participants: A purposive sample (n = 30) was drawn from the intervention group (n = 700) according to a range of responses to the trial baseline and follow up quantitative measures. Results: 28 interviews were included in the analysis. Compared with the previous system of fixed appointments, preference for the new open access system was based on enhanced personal control in contacting services and the view that it fitted better with everyday routine management and the requirement for urgent medical contact when symptoms fail to respond to medication. Preference for retaining fixed appointments was based on a sense of security from gaining access which did not require the individual to initiate the request for medical help. Conclusions: Open access may fit better with patients' self-management of their condition and everyday routines, roles and responsibilities. Ensuring that outpatient organisational arrangements and personnel are responsive to patient initiated requests for appointments is likely to impact on the acceptability of this type of access arrangement. Some people may continue to prefer the fixed appointment system which should be retained if patient choice is to be respected.